How do taxation and regulation affect the real estate market? - Mathias Dolls; David Gstrein; Carla Krolage; Florian Neumeier (EconPol Forum, 2022)
Rent caps can have significant unintended consequences through lower housing supply. Instead of making housing more affordable, purchase subsidies have provided a windfall for sellers. The real estate transfer tax levied on properties' purchase price substantially decreases property prices. The Covid-19 pandemic may leave long-lasting impacts on Germany's housing market. Policymakers would be well advised to take into account such trends and side effects when formulating policy
Keywords: 330